Architecture and Fault Identification of Wide-area Protection System - Zhenxing Li Zhenxing Li; Xianggen Yin Xianggen Yin; Zhe Zhang Zhe Zhang; Yuxue Wang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Wide-area protection system (WAPS) is widely studied for the purpose of improving the performance of conventional backup protection. In this paper, the system architecture of WAPS is proposed and its key technologies are discussed in view of engineering projects. So a mixed structure-centralized-distributed structure which is more suitable for WAPS in limited power grid region, is obtained based on the advantages of the centralized structure and distributed structure. Furthermore, regional distance protection algorithm was taken as an example to illustrate the functions of the constituent units. Faulted components can be detected based on multi-source imformation fuse in the algorithm. And the algorithm cannot only improved the selectivity, the rapidity, and the reliability of relaying protection but also has high fault tolerant capability. A simulation of 220 kV grid systems in Easter Hubei province showed the effectiveness of the wide-area protection system presented by this paper.